2017
DOI: 10.1159/000485537
|View full text |Cite
|
Sign up to set email alerts
|

Müller Cell-Derived PEDF Mediates Neuroprotection via STAT3 Activation

Abstract: Background/ Aims: This study was performed to reveal signaling pathways exploited by pigment epithelium-derived factor (PEDF) derived from retinal (glial) Müller cells to protect retinal ganglion cells (RGCs) from cell death. Methods: The survival of RGCs was determined in the presence of conditioned culture media (MCM) from or in co-cultures with Müller cells. The significance of PEDF-induced STAT3 activation was evaluated in viability assays and using Western blotting analyses and siRNA-transfected cells. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Both PEDF and VEGF-AA, which were found to be significantly upregulated after TNFα priming of MSCs, are known neuroprotective agents for injured RGCs. Müller cells exert a neuroprotective effect on RGCs through the secretion of PEDF, 39 while delivery of PEDF into retinal cultures or rat eyes after optic nerve crush leads to significant RGC neuroprotection. 40 Delivery of VEGF into ocular hypertensive eyes leads to significant RGC neuroprotection while also upregulating PEDF.…”
Section: Discussionmentioning
confidence: 99%
“…Both PEDF and VEGF-AA, which were found to be significantly upregulated after TNFα priming of MSCs, are known neuroprotective agents for injured RGCs. Müller cells exert a neuroprotective effect on RGCs through the secretion of PEDF, 39 while delivery of PEDF into retinal cultures or rat eyes after optic nerve crush leads to significant RGC neuroprotection. 40 Delivery of VEGF into ocular hypertensive eyes leads to significant RGC neuroprotection while also upregulating PEDF.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species lowering has shown to be helpful in protecting neuronal degeneration and favoring the expression of protective factors like compact myelin proteins [93]. Retinal ganglion cell survival is also promoted by PEDF (pigment epithelium-derived factor) via STAT3 (signal transduction and activator of transcription 3) activation secreted by Müller cells [94].…”
Section: Pathophysiology Of Diabetic Retinopathymentioning
confidence: 99%
“…Pigment epithelium-derived factor (PEDF), a 50-kDa secreted glycoprotein, is widely expressed throughout the body. Previous studies have shown its role in maintaining homeostasis, including neuroprotective, anti-oxidative, anti-inflammatory, anti-tumor and anti-angiogenic [10][11][12][13]. It was found in our previous research that PEDF induced CCMR vessels remodeling--a process known as "pruning", as manifested by increases in lumen diameter and the assembly of VE-cadherin.…”
Section: Introductionmentioning
confidence: 81%